Pelatihan Penyusunan Laporan Keuangan Neraca bagi UMKM DUIT - Vinola Herawaty; Ayu Aulia Oktaviani; Jul Seventa Tarigan; Ati Kushariani (Penerbit Goodwood, 2023)
Purpose: Improve knowledge and ability to record financial transactions in accordance with SAK EMKM and Improving knowledge and ability to prepare financial statements especially balance sheet as a basis for information for financial management. Method: Participants in this activity are MSME entrepreneurs who are members of DUIT in the North Kedoya area, West Jakarta. The training activity has been carried out on April 20, 2022. The method of implementing this training is in the form of presentation of material on the importance of financial management for businesses. Examples of recording financial transactions and balance sheet financial statements are also given in accordance with applicable SAK EMKM standards. At the end of the training session, participants were given the opportunity to discuss interactively with the presenters and be able to convey what obstacles they have been facing in financial management so that solutions and problem solving can be given. Results: The majority of participants already know the types of financial statements. A total of 31% is very agree, 50% agree, while the remaining 15% are neutral and 4% disagree. Most of the participants also claimed to have understood how to make financial reports especially balance sheet for business. However, the number of participants who have made a good balance sheet is known only as much as 19% strongly agree and 42% agree. The remaining 31% are neutral and 8% disagree. Conclusion: It is known that the majority of MSME entrepreneurs already have knowledge of the types of financial statements and know how to prepare financial report especially balance sheet, but the number of MSME entrepreneurs who have made good financial reports is still less. This is understandable because to implement the preparation of a good balance sheet is not easy, it requires a fairly good knowledge and understanding of accounting